Resilient modulus and cumulative plastic strain of frozen silty clay under dynamic aircraft loading - Xiaolan Liu; Xianmin Zhang; Xiaojiang Wang (SN Applied Sciences, 2021)
Article Highlights The empirical equation for resilient modulus and temperature is a segmented function; the segmentation point is − 5 °C. The empirical equation for resilient modulus and frequency is a segmented function; the segmentation point is 2 Hz. The cumulative plastic strain is positively correlated with temperature and negatively correlated with frequency.